(untitled) (Universitas Scientiarum, 2013)
We describe simple protocols for the extraction of total DNA and ctDNA from Passiflora species. Total DNA was purified from less than 40mg of different tissue sources (buds, tendrils, stipules, nodes or leaves) in the presence ofPVPP to avoid polyphenols. ctDNA isolation was based on the lysis of chloroplasts purified by sucrose step gradients. Up to 50mg of ctDNA were obtained from less than 20g ofleaf tissue. Both procedures yielded clean DNA suitable for PCR amplification and restriction endonuclease digestion. These techniques can be used for the analysis of DNA from single plants using small amounts of tissu